2019
DOI: 10.1016/j.heliyon.2019.e01804
|View full text |Cite
|
Sign up to set email alerts
|

Nanoencapsulated essential oils embedded in ice improve the quality and shelf life of fresh whole seabream stored on ice

Abstract: Ice containing essential oils (EOs) nanoencapsulated in β-cyclodextrins (β-CD) (named as EOs+β-CD ice) was used for stunning/slaughtering by hypothermia in ice slurry, and for ice storage of gilthead seabream. Clove essential oil (CEO) was used at fish stunning/slaughtering, while ice storage of whole fish was performed using a combination of carvacrol, bergamot and grapefruit EOs (CBG). Inclusion complexes CBG+β-CD were characterized, and antimicrobial effect was also evaluated. The kneading method used to fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 34 publications
2
11
0
1
Order By: Relevance
“…TMAB counts in the fresh fish are a useful tool for quality and shelf-life evaluation (Navarro-Segura, et al, 2019). As in the present study, Garrido, Hernández, Espinosa, & López (2016) reported the initial E. coli and LAB values were <1 log cfu/g for vacuumed sea bream.…”
Section: Microbiological Analysis Of Marinated Sea Bream By Processsupporting
confidence: 70%
See 2 more Smart Citations
“…TMAB counts in the fresh fish are a useful tool for quality and shelf-life evaluation (Navarro-Segura, et al, 2019). As in the present study, Garrido, Hernández, Espinosa, & López (2016) reported the initial E. coli and LAB values were <1 log cfu/g for vacuumed sea bream.…”
Section: Microbiological Analysis Of Marinated Sea Bream By Processsupporting
confidence: 70%
“…Lactic acid bacteria (LAB), total yeast and mold (TYM), total psychrophile aerob bacteria (TPAB), total anaerobic bacteria (TANB), and E.coli content of fresh sea bream muscle were below detectable values (<1 log cfu/g). Parlapani, Kormas, and Boziaris (2015) had reported the total microbial population of sea bream fillets initially as 4 log cfu/g Lower TMAB and TPAB counts of fresh sea bream muscle had been detected, for example, <3, 1.90 (except for TPAB), 0.37, 1–2 log cfu/g (except for TPAB) by different researchers (Carrascosa et al, 2015; Erkan and Üretener, 2010; Navarro‐Segura, Ros‐Chumillas, López‐Cánovas, García‐Ayala, & López‐Gómez, 2019; Song, Luo, You, Shen, & Hu, 2012). TMAB counts in the fresh fish are a useful tool for quality and shelf‐life evaluation (Navarro‐Segura, et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Table 1, EOs and plant extracts are often incorporated into packaging materials (e.g., chitosan and gum) or other media (crushed ice in ice‐storage), to lighten their negative impacts on food sensory quality. In the study of Navarro‐Segura, Ros‐Chumillas, López‐Cánovas, García‐Ayala, and López‐Gómez (2019) who used crushed ice containing encapsulated EOs to preserve whole sea bream, sensory panelists did not detect odor differences between control and EOs ice treated samples. In the study of Sun, Sun, Thavaraj, Yang, and Guo (2017), the initial color of grass carp surimi turned yellowish, after the treatment with apple polyphenol extract.…”
Section: Influencing Factors Of Microbiota Composition In Fish and Crmentioning
confidence: 97%
“…To investigate sensory acceptability, Navarro-Segura et al [176] studied the inclusion of nanoencapsulated essential oils into cyclodextrin films, and these authors concluded that the use of both strategies (nanoencapsulation and the film) improved the sensory acceptability and decreased microbiological counts and trimethylamine, so the shelf life was extended by 4 days. These authors reported an improvement in the sensory acceptability of seabream stored on ice and packaged with films (containing nanoencapsulated essential oils with cyclodextrin).…”
Section: Incorporation Of Thyme In Fish and Seafoodmentioning
confidence: 99%